Experimental Review on Influence of Inlet Disturbance Body (IDB) at 30° Against Inhibitory Force Reduction on Three Circular Cylinders with Composed of Stagger (Variation L/D(constant=2), T/D = 1.5, 2, 3 & 4). Issue 1 (June 2019) - Cut, B; Akram, R; Iskandar,; Rahman, A; Zulfri, M; Nazaruddin,
Abstract: Research on the characteristics of the fluid flow across the bluff body has been carried out and placed in a variety / setting, let alone research on fluid flow across three circular cylinder arranged stagger by placing 2 (two) Inlet Disturbance Body ( IDE ) as a bully in front. This effort is usually done to reduce the normal force, shear force, and drag force that occurs in the bluff body of the three circular cylinders. This research was conducted experimentally in mechanics laboratories and fluid machines using subsonic wind tunnels and tested at Re = 2.2x10 4 based on the diameter of a circular cylinder. Variations used are longitudinal distance ratio (L/D) = 2 with a circular cylinder diameter (D = 25 mm) and transverse distance ratio (T/D) = 1.5, 2, 3 and 4 and IDE placement on the upper and lower sides from cylinder 1 (upstream) in the form of a cylinder with a diameter (d = 4mm) at 30 °. The results showed that the use of IDB at position 30° can reduce the drag force that occurs in cylinder 1 (upstream) 36 to 53% compared to with no IDE, while for cylinder 2 (upstream), the drag is higher for (T/D) = 1.5, 2 and 3 are 3.2 to 22% and at (T/D) = 4 the drag force is reduced to 9% again. About cylinder 3 (downstream - down) in the stagger configuration with IDB 30°, the drag is 4.8 to 44% higher for all distance variations (T/D) compared to the stagger configuration with no IDE. Variation in distance (T/D) also greatly affects the distribution of pressure coefficients that occur with the three circular cylinders with a stagger arrangement, causing a difference in the distribution of the drag pressure coefficient ( Cdp ) and also the velocity profile behind the 3 circular cylinders with the stagger arrangement.